Health Risk Characteristic Due to Air Pollution Exposure in Shoe Soles Workers (around Bubutan Road in Surabaya city) - Rahmadani Rahmadani; Abdul Rohim Tualeka (JURNAL KESEHATAN LINGKUNGAN, 2016)
Abstract: Risk characterization is end of the risk assessment process. Toxin agent can enter the human body by inhalation process, skin (dermis) and digestion process. The objectives of this research is to determine risk characterization of exposure to air pollutans on the health of sole services worker. This study was an observational study with cross sectional approach. 25 people of this sampel study were the total population. Independent variabels were age, weight, lenght of work in this sector, lenght of exposure time, number of working days. Dependent variabels were the concentration of CO, SO2 and NO2. Data were analyzed descriptively and the result of the data would be narrated and shown on the frequency table. Result the exposure assessment of carbon monoxide parameter on sole services workers were gotten the highest intake value was 0.2028 mg/kg/day and the lowest value was 0.0085 mg/kg/day, sulfur dioxide parameter on sole services worker were gotten the highest intake value was 0.0004028 mg/kg/day and the lowest value was 0.0000169 mg/kg/day, nitrogen dioxide parameter on sole services worker were gotten the highest intake value was 0.01238 mg/kg/day and the lowest value was 0.00051 mg/kg/day. Based on the results of the research, it can be concluded that RQ < 1 showed that air quality is still safe. But, in fact is still founded the lamentation of the health disruption and the uncomfort air condition arround the survey area. Research of Refferences of Concentration (RfC) will be needed, especially for CO, SO2 and NO2 parameter fi t of the characteristic of Indonesian people and especially informal sector worker in Surabaya.Keywords: Risk Quotient, Exposure of CO, SO2 and NO2, Workers